PRACTICAL ASPECTS OF MEASURING CRITICAL GAPS AND FOLLOW-UP TIMES AT MEDIAN UNCONTROLLED T-INTERSECTIONS - Adrian BARCHAŃSKI; Renata ŻOCHOWSKA (Scientific Journal of Silesian University of Technology. Series Transport)
Estimation of critical gaps and follow-up times between vehicles at uncontrolled intersections is an essential step in estimating the capacity of these objects and assessment of traffic conditions. Therefore, measurements of these parameters should be properly prepared and implemented. This paper presents issues related to the performance of field tests at median uncontrolled T-intersection. Measurements included both critical gaps and follow-up times. Based on the collected material, the authors identified problems occurring during traffic observation. Analyzed intersections were located both within and outside built-up areas. Furthermore, this article discusses the influence of selected factors on the accuracy of estimating the critical gaps and follow-up times and formulates the principles of conducting traffic measurements at selected types of intersections.